SOCIAL, ECONOMIC, AND CULTURAL LIFE OF THE SURKHAN VALLEY DURING THE ASHTARKHANID PERIOD - Xursandova Kamola Azamatovna (Bright Mind Publishing, 2026)
At the end of the 16th century and the beginning of the 17th century, significant political changes took place in the history of Central Asia. As a result of the decline of the Shaybanid dynasty, a new political power—the Ashtarkhanids (or Janids) dynasty—came to power in the Bukhara Khanate. The rise of the Ashtarkhanids marked a new phase in the history of the Bukhara Khanate and led to significant changes in the state structure, governance system, and foreign policy. The coming to power of the Ashtarkhanid dynasty was a crucial turning point in the history of the Bukhara Khanate. This dynasty continued the state traditions established during the Shaybanid era but was forced to adapt to new political conditions. Through their rule, the Bukhara Khanate remained one of the important political centers in Central Asia throughout the 17th century. This article provides essential information about the socio-economic situation and cultural life of the Surkhan Valley during the Ashtarkhanid period, as well as about the defense system of the Denov fortress located in the valley.
Keywords: Chaganiyans, kharaj, Janids, Denov fortress, Surkhan-Boysun, “Alpomish”, local beyliks, epic poetry.